Measurement of the inclusive isolated-photon production cross section in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (SPRINGER, 2025)
The ALICE Collaboration at the CERN LHC has measured the inclusive production cross section of isolated photons at midrapidity as a function of the photon transverse momentum (p(T)(gamma)), in Pb-Pb collisions in different centrality intervals, and in pp collisions, at centre-of-momentum energy per nucleon pair of root s(NN) = 5.02 TeV. The photon transverse momentum range is between 10-14 and 40-140 GeV/c, depending on the collision system and on the Pb-Pb centrality class. The result extends to lower p(T)(gamma) than previously published results by the ATLAS and CMS experiments at the same collision energy. The covered pseudorapidity range is |eta(gamma)| < 0.67. The isolation selection is based on a charged particle isolation momentum threshold p(T)(iso,ch)=1.5 GeV/c within a cone of radii R=0.2 and 0.4. The nuclear modification factor is calculated and found to be consistent with unity in all centrality classes, and also consistent with the HG-PYTHIA model, which describes the event selection and geometry biases that affect the centrality determination in peripheral Pb-Pb collisions. The measurement is compared to next-to-leading order perturbative QCD calculations and to the measurements of isolated photons and Z(0) bosons from the CMS experiment, which are all found to be in agreement.
Keywords: QUARK-GLUON PLASMA; NUCLEAR MODIFICATION; BOSON PRODUCTION; PLUS; PERSPECTIVE; MATTER; HOT; Physics